Bevacizumab increases the risk of infections in cancer patients: A systematic review and pooled analysis of 41 randomized controlled trials. Issue 3 (June 2015) - Qi, Wei-Xiang; Fu, Shen; Zhang, Qing; Guo, Xiao-Mao
Abstract: Background: Bevacizumab, a recombinant humanized monoclonal antibody that targets the vascular endothelial growth factor, has been approved for use in a variety of malignancies. There have been reports of infections associated with the use of bevacizumab. We performed this meta-analysis to determine the overall incidence and risk of infections associated with bevacizumab in cancer patients. Methods: Pubmed and oncology conference proceedings were searched for relevant studies from January 2000 to June 2014. Studies were limited to phase II and phase III randomized controlled trials (RCTs) of bevacizumab in cancer patients with adequate safety profiles. Summary incidences, relative risks (RRs), and 95% confidence intervals (95%CIs) were calculated by using either random effects or fixed effect models according to the heterogeneity of included studies. Results: In total 33, 526 patients from 41 RCTs were included. The use of bevacizumab significantly increased the risk of developing all-grade (RR 1.45, 95%CI: 1.27–1.66, p  < 0.001) and high-grade (RR 1.59, 95%CI: 1.42–1.79, p  < 0.001) infections in cancer patients. Sensitivity analysis indicated that the significance estimate of pooled RRs was not significantly influenced by omitting any single study. On subgroup analysis, the risk of developing high-grade infection varied significantly with concomitant drugs ( p  = 0.008). When stratified according to specific infectious events, the use of bevacizumab significantly increased the risk of developing severe febrile neutropenia (RR 1.57, 95%CI: 1.34–1.84; p  < 0.001) and fistulae/abscesses (RR 2.13, 95%CI: 1.06–4.27; p  = 0.033). No evidence of publication bias was observed. Conclusions: Bevacizumab treatment significantly increases the risk of infectious events developing in cancer patients. The risk may vary with concomitant drugs. Clinicians should be aware of the risks of infections with the administration of this drug in cancer patients.